2022
DOI: 10.1155/2022/8112212
|View full text |Cite|
|
Sign up to set email alerts
|

Computer Security Issues and Legal System Based on Cloud Computing

Abstract: To effectively improve the security and accuracy of computer information storage, a computer security problem and legal system based on cloud computing are proposed. Firstly, this article details the evolution of cloud computing, its characteristics, architecture, and application status of cloud computing in detail. Second, we discussed security strategies to ensure the confidentiality and integrity of cloud computing information, focuses on the data encryption technology of cloud data security, and designs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Finally, the system is created in the laboratory and thoroughly tested. The test results reveal that the system in this work has a specific improvement in data transmission rate compared to the present generally used systems, but the use rate of node CPU is as high as 40%, which leads to certain demands for node CPU performance [18]. This article gives assessment findings for a high-security disaster recovery system that uses distribution and rake technology.…”
Section: Background and Related Workmentioning
confidence: 95%
“…Finally, the system is created in the laboratory and thoroughly tested. The test results reveal that the system in this work has a specific improvement in data transmission rate compared to the present generally used systems, but the use rate of node CPU is as high as 40%, which leads to certain demands for node CPU performance [18]. This article gives assessment findings for a high-security disaster recovery system that uses distribution and rake technology.…”
Section: Background and Related Workmentioning
confidence: 95%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%